PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI PEMBAYARAN SPP (SUMBANGAN PEMBINAAN PENDIDIKAN) DI SMK GEO INFORMATIKA KABUPATEN BOGOR BERBASIS WEB - Yanti, Dianah; Fauziyah, Fauziyah; Whendasmoro, Raditya Galih (LPPM Universitas Bina Bangsa, 2023)
Tuition payment is mandatory for every student or student, public or private school to support educational development. In schools SMK Geo Informatics has problems in SPP payments, namely: payment still uses a handwritten ledger, there can be duplication of data and the process still uses Ms.Excel without a database. Waterfall method is used. The tools used to create an Payment information system SPP are: Unified Modeling Language (UML), Visual Studio Code, Xampp, Bootstrap, and Microsoft Edge. The Payment information system SPP uses PHP (Hypertext Prepocessor) and MySQL programming languages. The result of the study was: recorded in the blackbox test with 20 valid tests. With the SPP payment information system application, it can run well in SMK Geo Informatics schools are able to handle late tuition payments and fast data search, and are easier to use